Effectiveness of Virtual Care Reality 360o on Suction and Oxygen Administration Skills with Precaution Standards for Nursing Students - Endang Triyanto; Lita Heni Kusumawardani; Muhamad Jauhar; Utami Rachmawati; I Gusti Ayu Putu Desy Rohana; Rasdiyanah Rasdiyanah (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2024)
Background: Current learning methods continue to develop, nursing students need effective learning methods to improve students' abilities and skills in achieving competencies, one of which is fulfilling human needs: oxygenation. Virtual care reality in 3600 video can be a real and concrete alternative learning method solution for students.Method: This research aims to determine the effect of virtual care reality in 3600 videos on skills in fulfilling basic human needs: oxygenation in nursing students. The research used a quasi experimental pre-post test design using a control group. The intervention group was given treatment in the form of Virtual Care Reality in video 3600 (VCR 3600) for 15 minutes at least three times in each video. VCR 3600 contains material about fulfilling basic human needs for oxygenation including suction, use of nasal cannulas, masks (Non-Rebreathing Mask/NRM and Rebreathing Mask/RM). Post-test measurements were carried out two weeks after the VCR 3600 intervention was carried out for the internalization phase first. The benefit of this research is that it is hoped that the VCR 3600 will be able to improve skills in fulfilling basic human needs: oxygenation in nursing studentsResults: The results of this study show that respondents are aged 18 - 20 years, with a median value of 19 years. The gender of the respondents was mostly female, the majority of respondents had never studied suction, the majority of respondents had never had experience studying material about administering oxygen therapy. The mean skills of suctioning and oxygen administration of respondents after the intervention in the intervention and control groups both increased. The results of further analysis showed that there was no significant difference in skills after the intervention between the intervention group and the control group (p value < 0.05).Conclusion: The results of the study showed that there was an increase in the skills of respondents after the intervention regarding suction and administering oxygen with standard precautions. Although there is no statistical effect of the VCR 3600 method on suctioning and oxygenation skills, the use of this method has the opportunity to increase students' knowledge and be used as a variation of practical learning methods.